2020
DOI: 10.1021/acs.inorgchem.0c01250
|View full text |Cite
|
Sign up to set email alerts
|

Vapor-Phase Infiltration inside a Microporous Porphyrinic Metal–Organic Framework for Postsynthesis Modification

Abstract: Vapor Phase Infiltration (VPI), a technique derived from Atomic Layer Deposition (ALD) and based on sequential self-limiting chemistry is used to modify the stable microporous porphyrin-based Metal Organic Framework (MOF) MIL-173(Zr). VPI is an appealing approach to modify MOFs by inserting reactants with atomic precision. The microporous nature and chemical stability of MIL-173 enable post-synthesis modification by VPI without MOF degradation even with extremely reactive precursors such as trimethylaluminum (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Previous study demonstrated an efficient diffusion of metallic precursors inside MIL-173 pores 45,48 .…”
Section: Resultsmentioning
confidence: 93%
“…Previous study demonstrated an efficient diffusion of metallic precursors inside MIL-173 pores 45,48 .…”
Section: Resultsmentioning
confidence: 93%
“…Given the impressive robustness of the Zr-gallate framework, this material was further studied by several groups for a number of properties. We could demonstrate its compatibility with an ALD-derived technique for post-synthesis modification on both the phenolic and pyrrolic reactive sites 112 . Vapour phase infiltration was achieved using two kinds of precursors: diethylzinc (DEZ) and trimethylaluminium (TMA).…”
Section: Phenolatesmentioning
confidence: 97%
“…Ideally, bridging or terminal hydroxo and/or aqua node ligands can react with metal ions, labile inorganic complexes, or organometallic complexes, either in the condensed phase (often termed solvothermal deposition in MOFs (SIM)) or via molecular volatilization into the vapor phase (often termed atomic layer deposition in MOFs (AIM)) to accomplish chemical attachment. [89][90][91][92][93][94][95][96][97] Subsequent treatment with steam or H 2 S can yield node-grafted oxy-or sulfido-metal species -either as individual metal ions or as few-atom clusters. 98,99 A majority of the transition-metal elements and a handful of main-group metals have now been grafted in this way to Zr-MOF nodes.…”
Section: Stabilizing and Presenting Catalystsmentioning
confidence: 99%